Utilization of solar panels as lighting in Puncak Anabawa, Rokan Hulu, Riau - Ridwan Sinurat; Nurhikmah Sasna Junaidi; Ahmad Fathoni; Suyitno Suyitno; Jeki Mediantari Wahyu Wibawanti; Murry Harmawan Saputra (Community Empowerment, 2023)
Puncak Anabawa is situated in Sialang Jaya Village, District Rambah, Kab. Rokan Hulu, Riau. The objective of this initiative is to enhance the tourism potential of Puncak Anabawa, positioning it as a preferred destination for tourists. One significant challenge faced by our partners is the lack of electricity and lighting sources at Puncak Anabawa, creating difficulties for tourists in finding essential services. To address this issue, we propose the use of solar panels as a sustainable source of electricity and lighting. The installed solar panels at Puncak Anabawa serve as an effective solution, providing power for visitors who come to camp or capture the scenic views at the peak. The execution of these activities involves site surveys, the assembly and installation of solar panels for lighting, and assistance with technology usage. Following the completion of these activities, the solar panels have been successfully installed and function as reliable lighting infrastructure at this tourist location.